Parental engagement in school-based health promotion and education. Issue 6 (6th November 2018) - Spencer, Grace; Hood, Philip; Agboola, Shade; Pritchard, Catherine
Abstract : Purpose: Children's health and life chances are affected by many factors, with parents and schools holding influential roles. Yet relatively little is known about parental engagement in school-based health education and specifically, from the perspectives of health and education professionals. The purpose of this paper is to examine professionals' perspectives on parental engagement in school-based health education. Design/methodology/approach: An exploratory qualitative study was conducted with ten health, education and local authority professionals from a socio-economically deprived area in England. Semi-structured interviews explored the role of professionals within the school health curricula, roles that parents played in school health, and barriers and enablers to parental engagement in school health education. Findings: Reported barriers to engagement related to assumptions about parents' own health behaviours, impacts of funding and inspection regimes, and protected time for health within the school curriculum. Enablers included designated parental support workers based in the school, positive role modelling by other parents, consultation and engagement with parents and a whole school approach to embedding health within the wider curriculum. Practical implications: Findings from this study suggest the importance of building meaningful partnerships with parents to complement school health education and improve child health outcomes. Originality/value: This paper addresses an important gap in the research on parental engagement in school-based health education from the perspectives of health and education professionals. Effective partnerships with parents are crucial to the success of school health education.